A Utilização de Ferramentas de Business Intelligence (B.I.) na Precificação - QUINTINO, Cesar Augusto Jangarelli; BRITO, Luciane Priscila Nunes de (275, 2025)
Este trabalho analisa o papel das ferramentas de Business Intelligence (B.I.) na otimização da precificação e no acompanhamento dos preços da concorrência, destacando sua relevância para o mercado. Com a crescente digitalização e a intensa competitividade, as empresas necessitam de estratégias mais ágeis e baseadas em dados para ajustar seus preços em tempo real e manter a compe- titividade. As soluções de B.I. permitem a coleta, análise e visualização de grandes volumes de dados internos e externos, como preços de concorrentes, demanda do mercado e padrões de consumo, proporcionando decisões estra- tégicas.

This paper analyzes the role of Business Intelligence (B.I.) tools in optimizing pricing and monitoring competitors' prices, highlighting their relevance to the market. With increasing digitalization and intense competition, companies re- quire more agile, data-driven strategies to adjust prices in real time and main- tain competitiveness. B.I. solutions enable the collection, analysis, and visual- ization of large volumes of internal and external data, such as competitors' prices, market demand, and consumption patterns, providing strategic deci- sion-making.
he Use of Business Intelligence (B.I.) Tools in Pricing: Analysis of Benefits and Challenges in the Current Competitive Environment.
Keywords: Concorrência; Preços; Informação e Comunicação